High altitude polycythemia and its maladaptive mechanisms: an updated review - Tang, Shijie; Zhou, Wenwen; Chen, Ling; Yan, Hui; Chen, Lei; Luo, Fengming (Frontiers in Medicine, 2024)
High altitude polycythemia is a maladaptation of highlanders exposed to hypoxic environment, leading to high blood viscosity and severe cardiorespiratory dysfunction. Prolonged hypoxia causes respiratory depression and severe hypoxemia, and further mediates changes in genetic and molecular mechanisms that regulate erythropoiesis and apoptosis, ultimately resulting in excessive erythrocytosis (EE). This updated review investigated the maladaptive mechanisms of EE, including respiratory chemoreceptor passivation, sleep-related breathing disorders, sex hormones, iron metabolism, and hypoxia-related factors and pathways.